Respostas

2013-04-25T01:55:42-03:00

 só trocar o x por -1;0;3 e 1;3

 

f(-1) = y = 3(-1) - 9 = -3-9=-12

x = -1

y = -12 

par ordenado : (-1;12)

 

f(0) = y = 3(0) - 9 = -9

 

x = 0

y = -9

par ordenado (0;-9)

 

f(3) = y = 3.3 - 9 = 0

 

x = 3

y = 0

par ordenado (3;0)

 

f(1/3) = y = 3.1/3 - 9 = -8

x = 1/3

y = -8

par ordenado (1/3;-8)

1 5 1
2013-04-25T10:21:36-03:00

a) f(-1) = 3*(-1)-9
f(-1) = -12

b) f(0) = 3*(0)-9
f(0) = -9

c) f(3) = 3*(3)-9
f(3) = 0

d) f(1/3) = 3*(1/2)-9
f(1/3) = 3/2 - 9
f(1/3) = -15/2

1 5 1